The Impact Of Credit Risk On The Profitability With Characteristics Bank As Control Variables - Rini Syahril Fauziah; Nur Hidayah K Fadhilah (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
The role of a bank cannot be separated from the existence of credit loans. On the other hand, credit loans will be profitable for banks but have the risk of default. In order to determine the extent of the influence of bad loans on return on assets with the characteristics of the bank as a controller in the banking sector listed on the Indonesia Stock Exchange in 2015-2019, this research is aimed at. Puposive sampling was chosen as a sampling technique where the data obtained were 23 companies with a 5-year observation period. The process of data analysis was carried out through multiple linear regression analysis. The statistical application used is the SPSS Statistic 25 application. The results found from this study, simultaneously bad loans have an influence on return on assets. Partially, net performing loans have a negative and significant effect on return on assets. Then, the Loan to Deposit Ratio has a positive and significant effect on the return on assets. The existence of the characteristics of the bank as a controller in this study has an influence on the relationship between the independent variable and the dependent variable.